This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
∣ ∣ ∣ x 2 − 5 x + 6 ∣ − ∣ 2 x − 4 ∣ ∣ ∣ ∣ ∣ ( x − 2 ) ( x − 3 ) ∣ − 2 ∣ x − 2 ∣ ∣ ∣ ∣ x − 3 ∣ − 2 ∣ = ∣ ∣ x 2 − 3 x + 2 ∣ ∣ = ∣ ( x − 2 ) ( x − 1 ) ∣ = ∣ x − 1 ∣
Let us assume that the maximum value of x satisfying the equation is > 0 .
For 0 < x ≤ 1 , { ∣ ∣ x − 3 ∣ − 2 ∣ = ∣ 3 − x − 2 ∣ = 1 − x ∣ x − 1 ∣ = 1 − x
Therefore, L H S = R H S ⟹ x ∈ ( 0 , 1 ] satisfies the equation.
For 1 < x ≤ 3 , { ∣ ∣ x − 3 ∣ − 2 ∣ = ∣ 3 − x − 2 ∣ = x − 1 ∣ x − 1 ∣ = x − 1
Again L H S = R H S ⟹ x ∈ ( 0 , 3 ] satisfies the equation.
For x > 3 , ⎩ ⎪ ⎨ ⎪ ⎧ ∣ ∣ x − 3 ∣ − 2 ∣ = ∣ x − 3 − 2 ∣ = { 5 − x x − 5 if x ≤ 5 if x > 5 ∣ x − 1 ∣ = x − 1
Therefore, L H S = R H S for x > 3 . And the maximum value of x satisfying the equation is 3 .